Reply to “Rational Bubbles in UK Housing Markets” - Giglio, Stefano; Maggiori, Matteo; Stroebel, Johannes (Econometrica, 2020)
In Giglio, Maggiori, and Stroebel (2016), we propose and implement a new test for classic rational bubbles. Such bubbles derive their value from each agent's rational expectation of being able to resell the bubble claims to the next agent. Backward induction ensures that classic rational bubbles can only exist on infinite‐maturity assets. Our empirical exercise shows that infinite‐maturity claims and 999‐year claims for otherwise identical housing assets trade at the same price, and thus rules out the presence of classic rational bubbles. Domeij and Ellingsen (DE) informally propose an alternative equilibrium of a bubble that they claim is consistent with our empirical findings. DE's bubble relies on information frictions such that market participants are unaware of the bubble. Our paper clearly excluded this type of bubble from the scope of our test, and DE's note thus has no implications for the validity of our test. Instead, DE's bubble simply represents one of many possible examples of bubbles on which our test was explicitly silent.